Do transnational corporations care about labour standards? - Matthias Busse (Hamburg Institute of International Economics (HWWA), 2002)
This paper explores the relationship between foreign direct investment, or the activities of transnational corporations, and core labour standards. It discusses the channels through which labour standards may influence foreign direct investment and presents the results of an empirical test of that linkage. The results show that, contrary to the conventional wisdom that transnational corporations engage predominately in countries with low standards, higher labour standards are positively associated with foreign direct investment inflows. Concerns about ,,social dumping“ or ,,a race to the bottom“ on such standards appear to be mistaken. This result even holds for poor developing countries. – – Die Beziehung zwischen ausländischen Direktinvestitionen, das heißt die Aktivitäten internationaler Konzerne, und grundlegenden Sozialstandards werden in dem vorliegenden Beitrag untersucht. Im Mittelpunkt dabei steht zum einen eine Diskussion möglicher Wirkungskanäle zwischen Sozialstandards und ausländischen Direktinvestitionen; zum anderen eine empirische Überprüfung dieser Zusammenhänge. Die Ergebnisse zeigen, dass internationale Konzerne überwiegend in Ländern investieren, die überdurchschnittlich hohe Sozialstandards aufweisen. Befürchtungen über ,,soziales Dumping“ oder eine wettbewerbsbedingte Verschlechterung der Standards nach unten sind demnach nicht zu erwarten. Dies gilt auch für relativ arme Entwicklungsländer.
Keywords: F23; O19; 330; Transnational Corporations; Foreign Direct Investment; Labour Standards; Cross-Country Regression Framework; Direktinvestition; Multinationales Unternehmen; Internationale Sozialstandards; Schätzung; Welt